Defibrotide for prophylaxis of hepatic veno-occlusive disease in paediatric haemopoietic stem-cell transplantation: an open-label, phase 3, randomised controlled trial - Corbacioglu, Selim; Greil, Johann (The lancet, 2012)
Summary: Background: Hepatic veno-occlusive disease is a leading cause of morbidity and mortality after haemopoietic stem-cell transplantation (HSCT). We aimed to assess whether defibrotide can reduce the incidence of veno-occlusive disease in this setting. Methods: In our phase 3 open-label, randomised controlled trial, we enrolled patients at 28 European university hospitals or academic medical centres. Eligible patients were younger than 18 years, had undergone myeloablative conditioning before allogeneic or autologous HSCT, and had one or more risk factor for veno-occlusive disease based on modified Seattle criteria. We centrally assigned eligible participants on the basis of a computer-generated randomisation sequence (1:1), stratified by centre and presence of osteopetrosis, to receive intravenous defibrotide prophylaxis (treatment group) or not (control group). The primary endpoint was incidence of veno-occlusive disease by 30 days after HSCT, adjudicated by a masked, independent review committee, in eligible patients who consented to randomisation (intention-to-treat population), and was assessed with a competing risk approach. Patients in either group who developed veno-occlusive disease received defibrotide for treatment. We assessed adverse events to 180 days after HSCT in all patients who received allocated prophylaxis. This trial is registered with ClinicalTrials.gov, number NCT00272948. Findings: Between Jan 25, 2006, and Jan 29, 2009, we enrolled 356 eligible patients to the intention-to-treat population. 22 (12%) of 180 patients randomly allocated to the defibrotide group had veno-occlusive disease by 30 days after HSCT compared with 35 (20%) of 176 controls (risk difference −7·7%, 95% CI −15·3 to −0·1; Z test for competing risk analysis p=0·0488; log-rank test p=0·0507). 154 (87%) of 177 patients in the defibrotide group had adverse events by day 180 compared with 155 (88%) of 176 controls. Interpretation: Defibrotide prophylaxis seems to reduce incidence of veno-occlusive disease and is well tolerated. Thus, such prophylaxis could present a useful clinical option for this serious complication of HSCT. Funding: Gentium SpA, European Group for Blood and Marrow Transplantation.